Overcoming Challenges with Performance Improvement Initiatives in Non-Profit Organizations to Achieve Sustainability Entity (Public Accounting and Sustainability, 2025)
Research aims: Elaborate on the operational challenges of non-profit organizations, and present performance optimization initiatives to achieve entity sustainability. Design/Methodology/Approach: This research uses a qualitative approach with the Focus Group Discussion (FGD) technique. The subjects in this study were all leaders and staff in one of the non-profit foundations in Yogyakarta, from which 10 informants were selected as samples. Research findings: This research successfully revealed that limited organizational capacity and technological infrastructure were serious challenges. This research also explains that capacity building and the application of solutive technology are strategic initiatives that can be chosen to optimize performance in fundraising efforts. Theoretical contribution/Originality: This research aims to elaborate on various operational challenges of non-profit organizations and deliver performance optimization initiatives to achieve entity sustainability. On the academic side, this research will elaborate on a sustainable management perspective that can provide additional knowledge. Practitioner/Policy implication: On the practical side, this research can provide various initiatives to maximize performance as a fundraising effort. Research limitation/Implication: The novelty of this research lies in the research object, which is a non-profit organization that has long been established and supported by the Yogyakarta Palace. This novelty is interesting because whether the support of the superpower institution will make it easier for this non-profit entity to get sympathy and assistance from fund donors.